Coordinated microbial lysis bursts into the drug delivery scene. Issue 3 (March 2023) - Sen, Sabyasachi; Kunjapur, Aditya M.
Abstract: To address limitations in dosing and releasing cargo from engineered microbes, Din et al. harnessed a previously designed oscillatory genetic circuit to achieve the synchronized release of cancer-killing protein payloads. Here, we briefly recap this study published in 2016 and its transformative impact on the field.